Requirements for balance setting-up and report improvement possibilities - Gipiene, G.; Matuseviciene, L. (Економічний вісник Донбасу, 2010)
Object of the article research is balance report. A theoretical research is done in the article where requirements of international and Lithuanian acts for balance content and form making are compared and differences between them are presented. Because it is assessed that balance is not informative enough balance improvement possibilities are introduced in the article by the authors. The article consists of introduction, two chapters, conclusion, and references. Key words: balance, IAS 1, Fourth Council Directive, BAS 2, improvement of balance sheet. Предметом статті є балансовий звіт. Авторами зроблено теоретичне дослідження, де порівняні міжнародні і литовські правові вимоги до змісту балансу та його форм, представлені їх відмінності. Оскільки баланс не є достатньо інформативним, автори статті представляють можливості поліпшення балансу. Ключові слова: баланс, 1-й МСФО, 4-а Директива Ради, 2-й БСБУ, поліпшення балансу. Предмет статьи — балансовый отчет. Авторами сделано теоретическое исследование, где сравнены международные и литовские правовые требования к содержанию баланса и его формам, представлены их различия. Поскольку баланс не является достаточно информативным, авторы в статьи представляют возможности улучшения баланса. Ключевые слова: баланс, 1-й МСФО, 4-я Директива Совета, 2-й БСБУ, улучшение баланса.